Advanced TiO2-polypyrrole nanostructures enhance glucose detection accuracy with cutting-edge non-enzymatic electrochemical capabilities - Ashima Thakur; Sweety Pal; Usha Sharma; Ajit Sharma; Meenakshi Choudhary; Mukesh C. Joshi; Herma Dina Setiabudi; Prabal Pratap Singh; Atheesha Singh; Sudheesh K. Shukla (Chemical Physics Impact)
High level of glucose in the blood lead to a serious disease especially in the heart, blood vessels, eyes, kidney & nerves etc. in human and thus its detection has an important aspect in medical sector and food industry as well. According to World Health organization (WHO), it was speculated that the number of overall diabetes's patient will increase globally by 2025. Thus, there is a notable need for the glucose sensors that may give quick response, extremely sensitive and economically sound to the regular blood glucose monitoring. In this study we have developed and deigned a cheapest, reliable and high performance TiO2-Polypyrrole (TiO2-PPy) nanocomposite based non-enzymatic electrochemical sensor for glucose detection. This hybrid nanostructured material has shown excellent electro catalytic properties toward glucose oxidation due to its high surface area. The resulting material were characterized by an optical and electrochemical techniques to validate its structural architecture and catalytic activity. Electrochemical studies revealed that the TiO2-PPy nanocomposite based sensor exhibited remarkable stability and sensitivity towards non-enzymatic glucose detection. The developed non-enzymatic glucose detection sensor demonstrated sensitivity of 678.57 μAmM−1cm2 with linear range of 0 mM to 5.5 mM The enhanced performance is attributed to the synergistic effects of both the metallic as well as polymer moieties in the nanocomposite, where polypyrrole provides an outstanding conductive network for an efficient electron transfer, while TiO2 offers an active Centre for oxidation of glucose molecule. Additionally, TiO2-PPy the sensor confirmed the excellent stability and reproducibility, along with strong potential for practical application in real sample analysis. Therefore, the proposed nanocomposite holds great promise for the development of sustainable and environmentally friendly glucose sensing devices.